The Impact of Anthropisation on the Floristic Composition, the Structure and Ecological Characterization of the Ngaoundr Cliff, Cameroon (Global Journal of Science Frontier Research, 2016)
A study was carried out on the impact of the anthropisation on woody vegetation of the Ngaoundere cliff. Its main objective was to assess the floristic composition, the structure and the ecological parameters of that vegetation. The research work was carried out on four formations of vegetation (fallows, fields, shrub savannahs, and arborescent savannahs). The floristic composition and structure vegetation were conducted on some plots of land covering 20m x 50m, giving a total of 24 ha on aggregate. The study of the data were done with the help of soft ware's like Excel, STATGRAPHICS plus 5,0 and XLSTAT all showed that the Ngaoundere woody vegetation shows an "L" structure under the influence of anthropic activities revealing a great number of waste and a small amount of mature stems. The specific richness is the most elaborate in savannahs planted with trees and the smallest in the fields and fallows lands. The Isoberlinia doka specie offers a comfortable ecological spectrum on the cliff even if it is running high risk of zooanthropic factors. The Cameroon Government should create and authenticate the cliff vegetation for a durable management.
Keywords: anthropisation; floristic; structure; ecological characterization; ngaoundere cliff